A importância do conhecimento Tácito no ensino de Língua Portuguesa - Sugui, Khalil Salem (2014)
This research investigates the value of tacit knowledge in education, especially as regards the teaching practice of portuguese language. For both elucidates the dimensions of both explicit knowledge as implicit knowledge, which is resize when one takes into account empirical and contextual aspects, whose structure builds new epistemological values, sometimes associated with the experience, sometimes articulated with prior knowledge. Indeed, the relevance of this research is due to the current overvaluation of explicit knowledge, which minimizes the importance of other potential gnosiological, such as intuition, and leads to the idea that many lessons are either totally right or totally wrong, deconstructing the principle of relativity and ponderability inherent epistemological act. It is intended, in this thesis, overcome this dualistic view, valuing, coherently, the tacit dimension of knowledge, as well as all other potential presents in this gnosiological plan. Indeed, in relation specifically to the linguistic study, this study is the assumption that every speaker has tacit knowledge of language and cognitive considers that such acquisitions can be used to advantage in the teaching and learning language process. Through a pedagogical look that enhances the personal aspects, and subsidiary tacit knowledge, we explore the importance of timely insight, intuition and discovery in the construction process of human knowledge, strengthening, thus, an organizational structure and articulated in terms the consolidation of skills and competencies consistent with the needs of today's knowledge society. The thesis draws upon theory in studies of Michael Polanyi, which mostly show the importance of tacit knowledge in human epistemological conformation. Other philosophers of science, such as Aristotle, Plato and Progogine are also used, in order to clarify, a dialogical way, the horizons of human knowledge as well as their internal dynamics and gradations. The research within the linguistic study bolsters on studies and concepts developed by Kleiman, Bechara, Chomsky and Van Dijk, seeking, according to these surveys, the values of key scoring tacit knowledge in the construction of linguistic knowledge